Nakaseke Telecentre (Uganda) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Nakaseke Telecentre has produced a CD-ROM, Rural Women in Africa: Ideas for Earning Money, in Luganda and English, with graphics and audio interfaces to facilitate its use by illiterate women.